An in-situ bio-remediation of nitrobenzene in stimulated aquifer using emulsified vegetable oil. (1st December 2021) - Dong, Jun; Ding, Linjie; Chi, Zifang
Abstract: Widespread nitrobenzene (NB) contamination in groundwater requires an economical and effective remediation technology. In situ microbial reactive zone enhanced by injecting emulsified vegetable oil (EVO) is an effective method for remediating NB-contaminated groundwater, which can be reduced to aniline (AN) effectively in the reactive zone. However, the bio-mechanism of NB remediation in a real contaminated site is still unclear. Thus, a 3-D tank was established to conduct a pilot-scale experiment and the bacterial communities in the tank were analyzed by 16S rDNA high-throughput sequencing. The results suggested that the injection of EVO can stimulate some certain microorganisms to grow, and reduce NB though biological and biochemical processes. There were three degradation pathways of NB: (1) direct oxidation by Pseudomonas ; (2) direct mineralization by Clostridium sensu stricto ; and (3) coupled reduction of NB through microbial dissimilatory iron reduction by Geobacter and Arthrobacter . Among these pathways, the coupled reduction process is the main degradation pathway. Graphical abstract: Image 1 Highlights: Emulsified vegetable oil can enhance nitrobenzene-contaminated groundwater remediation. Direct oxidation of nitrobenzene (NB) was achieved by Pseudomonas . Direct mineralization of NB was carried out by Clostridium . NB reduction coupled with microbial dissimilatory iron reduction was key process.